Discovery of pyrazolopyrimidine derivatives as novel inhibitors of ataxia telangiectasia and rad3 related protein (ATR). Issue 4 (15th February 2017) - Ramachandran, Sreekanth A.; Jadhavar, Pradeep S.; Singh, Manvendra P.; Sharma, Ankesh; Bagle, Gaurav N.; Quinn, Kevin P.; Wong, Po-yin; Protter, Andrew A.; Rai, Roopa; Pham, Son M.; Lindquist, Jeffrey N.
Graphical abstract: Abstract: The ATR pathway is a critical mediator of the replication stress response in cells. In aberrantly proliferating cancer cells, this pathway can help maintain sufficient genomic integrity for cancer cell progression. Herein we describe the discovery of19, a pyrazolopyrimidine-containing inhibitor of ATR via a strategic repurposing of compounds targeting PI3K.